Implementation of SRE as a solution for “IT lock-in” within the organization - Ryabukhin, Ilya (2024)
Current Information Technology (later referred as IT) infrastructure has been actively modernized by spending tremendous part of budget. It is evaluated as 6.9% of budget for companies less than $50 million of revenue, 4.1% for middle-sized companies ($50 million – $2 billion) and 3.2% for large companies (larger than $2 billion). These investments include infrastructure improving, hiring more IT specialists, and bringing innovative products with emerging technologies. However, it is seen that most of these companies are starting to lose their attention on core business and start to become an IT company (e.g., FinTech startup Revolut from Great Britain). This approach in long-term perspective may lead to the fact that Return Over Income (ROI) of IT investments would not work that much, because companies had started to utilize it more than core business, but at the same time their cash flow is coming not from IT, but from the core business part. As a solution for this there may be a concept called Site Reliability Engineering (later referred as SRE) that is now utilized as hardware acceleration and support methodology. However, that is not 100% correct, since this approach introduces a way to balance IT and Business interests. It helps to manage the budget, introduces the Service Level Objectives (SLOs) that are willing not to switch the focus into IT investments. As a master’s Thesis I am planning to accept or reject the hypotheses about the definition of collaboration of business with IT, as well as its relationship with IT vendor lock-in. For instance, the list of hypotheses looks like below: •“SRE adoption helps organization to stay Business-focused and not become solely IT-focused” based on real data.